Advanced High Voltage Power Device Concepts - Baliga, B. Jayant; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Advanced High Voltage Power Device Concepts describes devices utilized in power transmission and distribution equipment, and for very high power motor control in electric trains and steel-mills. Since these devices must be capable of supporting more than 5000-volts in the blocking mode, this books covers operation of devices rated at 5,000-V, 10,000-V and 20,000-V. Advanced concepts (the MCT, the BRT, and the EST) that enable MOS-gated control of power thyristor structures are described and analyzed in detail. In addition, detailed analyses of the silicon IGBT, as well as the silicon carbide MOSFET and IGBT, are provided for comparison purposes. Throughout the book, analytical models are generated to give a better understanding of the physics of operation for all the structures. This book provides readers with: The first comprehensive treatment of high voltage (over 5000-volts) power devices suitable for the power distribution, traction, and motor-control markets;  Analytical formulations for all the device structures with validation performed using numerical simulations; Analysis of potential silicon carbide structures that could compete with the silicon devices. Advanced High Voltage Power Device Concepts is an ideal book for researchers, engineers, and educators interested in emerging technology for renewable energy generation and distribution. This book provides readers with: The first comprehensive treatment of high voltage (over 5000-volts) power devices suitable for the power distribution, traction, and motor-control markets;  Analytical formulations for all the device structures with validation performed using numerical simulations; Analysis of potential silicon carbide structures that could compete with the silicon devices. Advanced High Voltage Power Device Concepts is an ideal book for researchers, engineers, and educators interested in emerging technology for renewable energy generation and distribution.
1 Introduction -- 2 Silicon Thyristors -- 3 Silicon Carbide Thyristors -- 4 Silicon GTO -- 5 Silicon IGBT -- 6 SiC Planar MOSFET Structures -- 7 Silicon Carbide IGBT -- 8 Silicon MCT -- 9 Silicon BRT -- 10 Silicon EST -- 11 Synopsis.
Keywords: Power electronics; Electronic circuits; Electronics; Microelectronics; Solid state physics; Power Electronics, Electrical Machines and Networks; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Solid State Physics